Study of Mixed Complexes of Cu(II) with Propylene Diamine, Malonate and Maleate Ions using Polarographic Technique - Paliwal, R.K. (Asian Journal of Chemistry, 2010)
The mixed ligand complexes of propylene diamine (pn), malonate (mal) and maleate (male) with Cu(II) have been studied polarographically at constant ionic strength, μ = 1.5 M (NaNO3) and pH 6.43 at 25.0 ± 0.1 ºC. The reduction of the complexes at d.m.e. is reversible and diffusion-controlled. One mixed complex [Cu(pn)(mal)] and [Cu(pn)(male)] is formed in each case with stability constants log β11 = 16.69 and 16.585 respectively.